1993
DOI: 10.1113/jphysiol.1993.sp019649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deoxygenation on active and passive Ca2+ transport and cytoplasmic Ca2+ buffering in normal human red cells.

Abstract: SUMMARY1. The effects of deoxygenation on cytoplasmic Ca2" buffering, saturated Ca2" extrusion rate through the Ca2" pump (Vmax), passive Ca2" influx and physiological [Ca2]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…8 and 9). These observations are consistent with earlier reports on an increase in free Ca 2ϩ concentration in the cytosol of RBCs undergoing deoxygenation in which hemoglobin gets protonated (65). Conformational changes responsible for these Ca 2ϩ -induced changes in oxygen affinity of hemoglobin await further characterization.…”
Section: Nmdar-induced Whole Cell Currents In Rbcssupporting
confidence: 81%
“…8 and 9). These observations are consistent with earlier reports on an increase in free Ca 2ϩ concentration in the cytosol of RBCs undergoing deoxygenation in which hemoglobin gets protonated (65). Conformational changes responsible for these Ca 2ϩ -induced changes in oxygen affinity of hemoglobin await further characterization.…”
Section: Nmdar-induced Whole Cell Currents In Rbcssupporting
confidence: 81%
“…1-3). A similar observation in AA RBCs ( 18) was explained by changes in both the proton ratio (r), which determines the equilibrium partition of [Ca2+ ]1 and [Ca2+]i, and in the ionized fraction of cell calcium, a, which reflects Ca2' buffering. The change in r on RBC deoxygenation can be calculated from measurements of cell and medium pH.…”
Section: Methodsmentioning
confidence: 92%
“…The results indicated that (a) each deoxy pulse caused a reversible increase in Ca 2ϩ permeability, P sickle-Ca , which lasted for the duration of the pulse; (b) the presence of external Ca 2ϩ caused K Ca channel activation in a fraction of cells (activated cells); (c) the fraction of activated cells increased within ‫ف‬ 30 min to plateau values between 10 and 45% in different experiments at physiological external Ca 2ϩ concentrations; (d) the plateau was constant for at least 3 h, and of similar value in consecutive pulses; (e) the fraction of activated cells was determined randomly in each pulse and did not reflect the response of a particularly vulnerable subpopulation of cells; (f) the plateau fraction of activated cells increased monotonically with [Ca 2ϩ ] o along a curve which reflected the distribution of P sickle-Ca in the cell population; this distribution indicated that the P sickle-Ca generated in each deoxy pulse varied widely among the cells, with the majority of cells having a value too low for K Ca channel activation at physiological [Ca 2ϩ ] o ; (g) as expected from the stochastic nature of P sickle-Ca , frequent deoxy-oxy pulsing was more efficient in generating larger fractions of dense cells than single deoxygenation pulses; and (h) in the fraction of cells with the highest P sickle-Ca Ca) influx was measured as previously described (9,19). Cells suspended at 10% Hct in solution B supplemented with inosine and pyruvate were equilibrated in the tonometer at 37ЊC, oxy or deoxy.…”
Section: Discussionmentioning
confidence: 99%
“…Loading of red cells with the Ca 2 ϩ chelator benz2 and measurements of their Ca 2ϩ ( 45 Ca) uptake were performed as previously described (9,14,19).…”
Section: Methodsmentioning
confidence: 99%